Applications, Smart Phones and Value Assessment: Digital Information in Academic Studies - Garai, Anna; Nádai, Julianna (European Journal of Sustainable Development, 2014)
In our presentation we focus on ways of decision mechanism how university students can evaluate the authenticity of digital information. To have a deep insight we made questionnaires which are the most appropriate way to get a big amount of relevant information on the research focus, in a relatively economic form. It is an underresearched, unrevealed area and a key issue as we do not have a wide knowledge of value systems of mobile internet users, the relationship between phone and computer applications and learning processes. Present statistics and social science publications are mainly focused on the increasing number of technical communication devices, that of applications and frequency of checking websites, but no research is made on users’ evaluation mechanism. Based on our questionnaires completed by university students we try to answer questions like how can students decide on authenticity of digital information? How can they use it efficiently for their studies? Based on the results you have the opportunity to develop new teaching methods in academic education for the future.